A conserved enzymatic toolkit targeting host cell metabolism is associated with Cryptococcus neoformans intracellular survival in protozoal and mammalian phagocytic cells - Dragotakes, Quigly; Jacobs, Ella; Gerbig, Gracen; Greengo, Seth; Jedlicka, Anne; Dziedzic, Amanda; Casadevall, Arturo (PLOS Pathogens, 2025)
Author summary A fundamental problem in the field of microbial pathogenesis is the mechanism by which microbes can cause disease in diverse hosts. In contrast to specialized pathogenic microbes that have an association with single or few hosts, generalist-type pathogens must survive in diverse hosts and thus must have non-specialized strategies to subvert cellular defenses, such as phagocytic cells. In this study we analyzed the interaction of the human pathogenic fungus Cryptococcus neoformans with amoeba and mouse and human macrophages, each phagocytic cell, comparing fungal proteins released into these cells after ingestion as well as transcriptional changes. C. neoformans is a generalist-type pathogenic fungus capable of causing diseases in mammals, fish, reptiles and insects. Despite the phylogenetic differences between these three types of phagocytic cells, their interaction with C. neoformans was remarkably similar. The results are consistent with the hypothesis that for C. neoformans the capacity for mammalian virulence emerged accidentally from selection pressures driven by phagocytic predators in soils such as amoeba. Furthermore, the results imply the existence of a conserved cryptococcal toolkit in the form of released proteins that enhance intracellular fungal cell survival by altering host phagocytic cell metabolism.